2013
DOI: 10.1192/bjp.bp.112.123182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 2-year multimodal intervention for disruptive 6-year-olds on substance use in adolescence: randomised controlled trial

Abstract: Adolescent substance use may be indirectly prevented by selectively targeting childhood risk factors that disrupt the developmental cascade of adolescent risk factors for substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
(56 reference statements)
3
27
0
Order By: Relevance
“…Most importantly, perhaps, is that this elevated risk was manifested well in advance of the normative trends in alcohol use that are characteristic of late adolescence. Clearly these youth are the strongest candidates for targeted early interventions (van Lier et al, 2009, Castellanos-Ryan et al, 2013), and programs that aim to reduce delinquency may result in delayed drinking onset or reduced rates of risky drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, perhaps, is that this elevated risk was manifested well in advance of the normative trends in alcohol use that are characteristic of late adolescence. Clearly these youth are the strongest candidates for targeted early interventions (van Lier et al, 2009, Castellanos-Ryan et al, 2013), and programs that aim to reduce delinquency may result in delayed drinking onset or reduced rates of risky drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Possible interventions and reducing externalizing behavior at 7-8 years of age may assist in reducing substance use behaviors during the peak of adolescence [10] or interventions targeted at reducing exposure in other adolescent drug users. We note that Figure 1 Longitudinal analysis of the Northern Finland Birth Cohort (NFBC) data for total drugs (Poisson path model).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PEMCS is associated with higher rates of externalizing behavior in pre-schoolers [4] and adolescents [5][6][7], as well as brain variations in young adults similar to those observed in attention deficit hyperactivity disorder [8]. Furthermore, developmentalcascade theories suggest etiological connections between externalizing behavior and substance use [9,10]. While this mediation pathway is clearly implicated, no studies have evaluated it formally.…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up of the boys during adolescence indicated that the preventive intervention between 7 and 9 years of age had reduced the number of aggressive kindergarten boys who were placed out of an age-appropriate regular classroom (Tremblay, Pagani-Kurtz, Mâsse, Vitaro, & Pihl, 1995), the frequency of physical aggressions and thefts between 11 and 17 years of age (Lacourse et al, 2002), and the frequency of substance use between 14 and 17 years (Castellanos-Ryan, Séguin, Vitaro, Parent, & Tremblay, 2013;Tremblay, Mâsse, Pagani, & Vitaro, 1996). When the boys turned 24 years of age, we collected data on high-school completion and crime data from courts.…”
Section: Helping Boys With Chronic Physical Aggression During the Elementioning
confidence: 99%